Structural Equation Model of Tourism Communication, Community Management, and Responsible Tourism Affecting Sustainable Tourism - Kongdee, Chatchawee; Cheyjunya, Patchanee; Taiphapoon, Tatri (Journal of Applied Economics and Management Strategy, 2020)
This study was conducted to determine tourism communication factors including direct and indirect influence of tourism communication factors and developing and validating the consistency of the measurement model and structural equation model for tourism communication factors, community management in tourism, responsible tourism, and sustainable tourism of communities at the Koh Lanta, Krabi Province and communities at Koh Yao Noi, Phang Nga Province. The samples composed of a community tourism network / network leader, the community leaders, tourism business operators including hotel operators, accommodation, food and beverage, souvenirs, tour and transportation companies, local administrative organizations, provincial government officials, state enterprises, educational institutions, private sectors and people in the area. There are 260 samples of Koh Lanta and 259 samples of Koh Yao Noi. A total of 519 samples are provided for comprehensive information and has a ratio corresponding to the population in the area. This research uses mixed method research methodology between qualitative method, document data collection, in-depth interviews by using a semi-structured interview as a tool for data collection and quantitative method by using survey research and closed-end questionnaires as a tool for data collection. The qualitative research results are applied for developing tools and structural equation model (SEM) in order to examine the consistency of the research model and data in the area. For quantitative research, data analysis with Inferential statistics by estimating model parameters with the maximum likelihood estimates method and using 13 index values to examine the consistency of the SEM with empirical data. The research findings indicate that all latent variables of the measurement model for tourism communication factor, community management in tourism, responsible tourism affecting sustainable tourism of both communities is consistent with empirical data because the observed variables are statistically significant at the level of .01 for all variables. The structural model is also consistent with the empirical data because more than 3 index values have passed the specified criteria. Direct and indirect influence analysis and the total influence of various variables in the SEM shows that the SEM developed by the researcher is consistent with the empirical data. This study results show that communication factors, community management in tourism, and responsible tourism affecting sustainable tourism.